Implementing Picture Based Activities to Enhance the Students’ English Writing Skill - Hasman, Hasman; Khadijah Maming; Sudarmanto; Mutiara Khadijah Tasha (Edumaspul: Jurnal Pendidikan, 2026)
This research is based on students’ writing skill before and after writing picture based texts with some given themes. The purpose of this research is to find out whether image-based activities can improve the writing skill of grade 8.2 students at UPTD SMP Negeri 11 Parepare after being given treatment picture based activities in writing English texts.The researcher used a descriptive quantitative pre-experiment design. This research was conducted for five meetings. The first meeting was the pre-test, the next three meetings were the treatment, and the last meeting was the post-test. The population of this study was students UPTD SMP Negeri 11 Parepare. While the sample consisted of 11 students from VIII.2 classes who were taken as samples using total sampling.The results of quantitative descriptive analysis showed that students’ writing skill improved when using picture based activities. This result was shown by the average score of Pre- test (34.54) and Post-test (81.36). After conducting the t-test calculation, the researcher found that the Null Hypothesis (H0) was rejected and the Alternative Hypothesis (H1) was accepted. This means that the use of Picture based activities as media can improve students’ writing ability in writing English texts.